المنهج بين فرانسيس بيكون وكارل بوبر دراسة تحليلية مقارنة - مهدي, غادة عبد الستار (lark, 2019)
Abstract:  We know what does it mean method , its mean that the manner or research way , which tries to find and discoverable way to reach to the real truth . And this way is very important for any philosophers or scientists . There are many methods not only one , because that the all sciences different, so the methods than more one. In this research I'll explain define method, their kinds and method between Frances Bacon and Karle popper. I mean which one more important in this period – Contemporary Ages – in scientific research. Finally who is one had improved scientific fields.